The Role of Health Care Services in the Isolation of the Elders of Moose Factory - Azzarello, Mary Ann (My University, 1997)
This thesis explores how formal health care services contribute to the isolation of some elders in the community. In Moose Factory 3 main aspects of the service system are identified as barriers to integrating the elders: Co-ordination of services, continuity of care and cross-cultural sensitivity. This formal system is examined in conjunction with the informal system of care which struggles to meet the elders' needs. The building of a long term care facility, while a practical solution may further isolate elders from the community and younger generations, enhancing the gap between generations. The model of cultural continuity is a framework that depicts elders as the conveyors of culture and points to the importance of maintaining cross-generational relationships. The profile of an elders liaison to the community is a tool that in future studies could be useful in identifying elders who are at risk of becoming isolated.
Keywords: Anthropology; Anthropology